Enthesopathy and involvement of synovio-entheseal complex in systemic sclerosis: an ultrasound pilot study. (13th August 2019) - Terenzi, Riccardo; Karalilova, Rositsa; Lepri, Gemma; Bruni, Cosimo; Bellando-Randone, Silvia; Manetti, Mirko; Romano, Eloisa; Melchiorre, Daniela; Blagojevic, Jelena; Wang, Yukai; Solanki, Kamal; Moggi-Pignone, Alberto; et al.
Abstract: Objectives: SSc is a chronic autoimmune disease characterized by inflammation of the skin and multiple internal organs. Articular involvement is one of the main features of SSc, and typical hallmarks of SpA have been found in SSc patients. The aim of the present study was to estimate the prevalence of entheseal and synovio-entheseal complex (SEC) alterations in a cohort of SSc patients. Methods: One hundred SSc patients and 25 healthy subjects were included in this cross-sectional study. The enthesis sites of lateral epicondylar common extensor tendons (CET) and the enthesis of the Glasgow Ultrasound Enthesis Scoring System were evaluated. SEC involvement was evaluated only at CET enthesis. Results: In SSc, the Glasgow Ultrasound Enthesis Scoring System score was significantly higher (median 4.0, interquartile range 2.0–7.0) than in controls (median 1.0, interquartile range 0.0–3.0) ( P < 0.0001). CET enthesis of SSc patients showed more frequent US B-mode alterations than that of controls (χ 2 = 11.47, P = 0.0007 for size; χ 2 = 13.79, P = 0.0002 for cortical irregularity, χ 2 = 5.24, P = 0.022 for calcification/enthesophytes). Power Doppler US signal at CET enthesis was significantly more frequent in SSc patients than in healthy controls (χ 2 = 9.11, P = 0.0025), as was the concomitant SEC involvement (χ 2 = 8.52, P = 0.0035). Conclusion: These data show that SSc patients frequently present US features of enthesopathy. Moreover, CET enthesopathy was correlated with SEC inflammation, suggesting that entheseal inflammation in SSc may share the same micro-anatomical targets as found in SpA.